Synthesis and characterization of 5, 7-dihydroxyflavanone derivatives as novel protein tyrosine phosphatase 1B inhibitors. (December 2013) - Sun, Liang-Peng; Ma, Wei-Ping; Gao, Li-Xin; Yang, Ling-Ling; Quan, Ying-Chun; Li, Jia; Piao, Hu-Ri
Abstract : A series of 5, 7-dihydroxyflavanone derivatives were synthesized and identified as reversible and competitive protein tyrosine phosphatase (PTP) 1B inhibitors with IC50 values in the micromolar range. Compound4k had the most potent in vitro inhibition activity against PTP1B (IC50 = 2.37 ± 0.37 μM) and the greatest selectivity (3.7-fold) for PTP1B relative to T-cell protein tyrosine phosphatase. Cell-based studies revealed that4k was membrane-permeable and enhanced insulin receptor tyrosine phosphorylation in CHO/ h IR cells.